‘I Don’t Want to Say Goodbye’: A Case Report of a Man’s Journey Through Complicated Grief - Voon, Siok Ping; Ting, Chuong Hock (Fakulti Perubatan dan Sains Kesihatan, UPM, 2024)
This case study illustrates the grieving journey of a 40-year-old Malaysian Chinese man who experienced physical and mental complications after the death of his loved one from lung cancer. This study included a description of a grieving individual with a clinical history of diagnoses and treatments to address his grief. The intervention integrated several modalities and techniques to facilitate behavior change and the healthy grieving process including pharmacotherapy and culturally-sensitive grief-focused therapies. This case study elucidates the integrative strategies while working with a client who had complicated grief. The outcome of the study provides evidence in support of the combination of pharmacotherapy and counseling. Recommendations and conclusions of the study are presented